New challenges for knowledge : digital dynamics to access and sharing - Fabre, Renaud; Messerschmidt-Mariet, Quentin; Holvoet, Margot (London : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2016)
Digital technologies are reshaping every field of social and economic lives, so do they in the world of scientific knowledge. "The New Challenges of Knowledge" aims at understanding how the new digital technologies alter the production, diffusion and valorization of knowledge. We propose to give an insight into the economical, geopolitical and political stakes of numeric in knowledge in different countries. Law is at the center of this evolution, especially in the case of national and international confusion about Internet, Science and knowledge.
6.2. Exchange platforms and catalogs6.3. Knowledge-processing and digital editions; PART 2: Sharing Mechanisms: Knowledge Sharing and the Knowledge-based Economy; 7. Business Model for Scientific Publication; 7.1. The current economic model is changing so as to adapt to new conditions for knowledge sharing; 7.1.1. A former model currently under discussion; 7.1.2. A model changed drastically by the presence of NICTs; 7.2. Creation of a new model ; 7.2.1. Toward a so-called "open process"?; 7.2.2. Moving toward open access; 7.3. The issues raised by the creation of a new economic model.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Knowledge management; Knowledge Management; Gestion des connaissances; COMPUTERS -- Information Technology; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Knowledge management